Some ethical dilemmas of modern banking. (13th May 2013) - Bagus, Philipp; Howden, David
Abstract : How ethical have recent banking practices been? We answer this question via an economic analysis. We assess the two dominant practices of the modern banking system – fractional reserves and maturity transformation – by gauging the respective rights of the relevant parties. By distinguishing the legal and economic differences between deposit and loan contracts, we determine that the practice of maturity transformation (in its various guises) is not only ethical but also serves a positive social function. The foundation of the modern banking system – the holding of fractional reserves against deposits – is, however, problematic from economic, legal and ethical perspectives. Starting from a microanalysis of money's function, a reassessment of the current laws concerning the practice is encouraged, with the aim not only to rectify economic irregularities but also to realign depositors' rights with the obligations of the banking sector.